Determining the Truth of Abuse in Mission Communities: A Rejoinder and New Agenda - Evinger, James S. ca. 20./21. Jh. (Christian scholar's review, 2014)
A previous article, “Christian Communities and ‘Recovered Memories’ of Abuse” (CSR 41.4 [2012]: 381-400) by Robert J. Priest and Esther E. Cordill, examines the problem of individuals wrongfully found to have committed abuse against minors in a mission context. However, James Evinger and Rich Darr argue the article erroneously describes the methodology of one denomination’s inquiry cited to support their argument, impugning the inquiry’s credibility. Additionally, the singular focus on recovered memories as a form of evidence diverts attention from matters deserving consideration for determining the truth of abuse. They offer a critique and propose a more effective way to achieve just responses when abuse in missionary communities is alleged.